Respuesta :

Answer:

[tex]\longrightarrow 5n+1\longleftarrow[/tex]

Step-by-step explanation:

[tex]f(n)=2n+1\\\\g(n)=3n\\\\f(n)+g(n)=?\\\\\longrightarrow (2n+1)\longleftarrow\\\\+\longrightarrow (3n)\longleftarrow\\\\f(n)+g(n)=2n+1+3n\\\\=(2n+3n)+1\\\\=(2+3)n+1\\\\=5n+1\longleftarrow \\\\\dagger[/tex]

Answer:

[tex]\boxed {\tt f(n)+g(n)=5n+1}[/tex]

Step-by-step explanation:

We want to find f(n) + g(n) . Basically, we have to find the sum of f(n) and g(n).

[tex]f(n)+g(n)[/tex]

We know that:

[tex]f(n)=2n+1\\g(n)=3n[/tex]

Therefore, we can substitute 2n+1 in for f(n) and 3n in for g(n)

[tex](2n+1)+(3n)[/tex]

Combine like terms. The terms 3n and 2n both have a "n" so they can be combined.

[tex](2n+3n)+(1)[/tex]

[tex](5n)+1[/tex]

[tex]5n+1[/tex]

f(n)+g(n) is equal to 5n+1